In Vitro Model to Evaluate the Development of Discolorations on Human Enamel Caused by Treatment with Mouth Rinses and Black Tea Considering Brushing - Sarembe, Sandra; Michler, Nicole; Ufer, Carolin; Kiesow, Andreas (European Journal of Dentistry, 2024)
Objectives The study aimed to develop and test an in vitro model to investigate the staining potential of mouth rinses on human enamel, considering alternating intake of black tea and tooth brushing, thus mimicking the situation in the oral cavity more realistically.Materials and Methods Eight mouth rinses with six different active ingredients (benzydamine hydrochloride [BNZ], polyhexamethylene biguanide hydrochloride [PHMB], chlorhexidine digluconate [CHX], hexetidine gluconate [HEX], octenidine dihydrochloride [OCT] and octenidine dihydrochloride + 2-phenoxyethanol [OCTP]) and concentrations were tested. Sets of six halved human molar crowns were initially pretreated by soaking in artificial saliva (30 min). Afterward, the cyclic treatment was started by soaking in artificial saliva (2 min), staining with black tea (1 min), brushing with toothpaste (5 s), and soaking in the mouth rinse (30 s). Samples were rinsed with distilled water after each treatment step. The cyclic treatment was repeated 30 times, mimicking the consumer behavior after 15 days. Photographic images were taken after 0, 10, 20, and 30 cycles. Color measurements were conducted after each staining and brushing step using a VITA-Easyshade spectrophotometer to determine the difference in lightness ∆L and the total color difference ∆E.Statistical Analysis Analysis of variance and post-hoc Tukey test (α = 0.05) were applied.Results The new testing model with included brushing sequences allowed to assess the staining behavior on human teeth and provided a clear differentiation between the different investigated products. In detail, up to cycle 10, ΔE values increased for all mouth rinses with each additional cycle number. However, while ΔE values continued to increase for 0.15% BNZ, 0.1% PHMB, and 0.2% CHX between treatment cycle 10 and 30, ΔE values only slightly increased after treatment with 0.08% OCTP, 0.1% OCTP, 0.1% OCT, and 0.1% HEX. After 20 and 30 cycles, significantly less staining was found for 0.08% OCTP, 0.1% OCT, 0.1% HEX as compared to 0.2% CHX, 0.15% BNZ, and 0.1% PHMB (p < 0.05). ΔE-values were significantly lower after treatment with 0.1% OCTP as compared to 0.2% CHX1 and 0.2% CHX2 (p < 0.05).Conclusion The proposed new methodology was found to be appropriate for assessing the staining progression of mouth rinses over a simulated application period of 15 days. The model allows differentiation of products with different active ingredients and concentrations.
Keywords: octenidine; chlorhexidine; benzydamine; polyhexamethylene biguanide; hexetidine; staining; black tea; tooth color